Material particulado, microbiota aérea e perfil de resistência de Staphylococcus aureus em suspensão durante o intra-operatório de cirurgias ortopédicas em um hospital de médio porte de São Carlos, SP - Almeida, Cristiane Leite de (2010)
The control of surgical site infection, especially during clean is important, especially when exposed bone in orthopedic surgery. A study was conducted exploratory study aimed to assess the impact of particulate matter, air and microbial resistance profile of Staphylococcus aureus in suspension for the intraoperative orthopedic procedures in a medium-sized hospital in São Carlos, SP. In the initial ten samples, the results indicate presence of filamentous fungi in 69% of the samples and 93.75% of the bacterial samples were identified as Gram positive and Gram negative 6.25%. In the 10 samples analyzed in the second stage, the UFC's of bacteria had an average of 97.80%, standard deviation of 51.60%, coefficient of variation of 52.75% and range between 21 and 178. We identified the presence of Staphylococcus aureus, Staphylococcus spp. and Shigella spp. 25%, 75% and 25% of samples, respectively. Held an antibiotic for Staphylococcus aureus isolated from the air in the operating room, and found that the strain had high levels of resistance to most antibiotics used, with sensitivity only two of 15 antimicrobial agents tested. The presence of suspended particles was above the recommended standard for the surgery, suggesting the need for an effective control of air quality. It was observed that during surgery there was a significant increase in suspended particles in accordance with WHO standards and CONAMA. The increase in the number of the surgical team in the room probably generated an increase of suspended particles and hence an increase in microbial range. Of the surgeries performed, one can see that in 70% of the operating room door was closed and 50% with air conditioning was off. In 3 (60%) of surgeries in which the air conditioning was off, we found the incidence of a bacterial genus.